Analytical investigation into the flexural behavior of steel tubular truss-and-concrete (STTC) composite beams. (April 2023) - Hu, Bo; Che, Ruiyu; Wang, Jingfeng; He, Xiaogang; Li, Lei; Kundu, Tribikram
Abstract: In this paper, experimental studies and numerical analyses are carried out to investigate the flexural performance of steel tubular truss-and-concrete (STTC) composite beams. A set of STTC composite beams were subjected to static loadings. The experimental procedures and the main test results are briefly presented. Then a finite element modeling strategy for STTC composite beams was developed, and its validity and accuracy were verified by test results. An extensive parametric analysis was performed to gain insight into the influence of 12 main parameters on the flexural response of STTC composite beams. Eventually, the prediction method for flexural stiffness and strength of STTC composite beams was verified based on the numerical simulation results. These experimental studies and numerical analyses can lead to improvements in the practical design of STTC composite beams.